Preparation and Characterization of Potato Starch Nanoparticles with Acrylamide by Microwave Radiation. - RODRIGUEZ PINEDA, LINA MARIA; Muñoz-Prieto, Efrén de Jesús; Rius-Alonso, Carlos A.; Palacios-Alquisira, Joaquín (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this study on decreasing the particle size of the potato starch, ultrasound and acid hydrolysis methods were carried out at the same time. The starch nanoparticles obtained were modified with acrylamide(AM) monomer by microwave irradiation, employing a small concentration of chemical initiator. It was found that, with a low concentration of potassium persulfate (PPS) in aqueous medium and microwave assistance, starch nanoparticles grafted with acrylamide could be prepared quickly. Native starch, starch nanoparticles and grafted copolymers were characterized by various analytical techniques. The Fourier transform infrared spectroscopy (FT-IR) analysis demonstrates group acrylamide attachment to starch nanoparticles chains. X-ray diffraction (XRD) and scanning electron microscopy (SEM) demonstrate an increased amorphous region of starch nanoparticles and grafted copolymers, while the thermogravimetric analysis (TGA) highlighted the increase in thermal stability of the copolymers in comparison to potato starch nanoparticles.